If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-5)=5
We simplify the equation to the form, which is simple to understand
6(x-5)=5
Reorder the terms in parentheses
+(+6x-30)=5
Remove unnecessary parentheses
+6x-30=+5
We move all terms containing x to the left and all other terms to the right.
+6x=+5+30
We simplify left and right side of the equation.
+6x=+35
We divide both sides of the equation by 6 to get x.
x=5.8333333333333
| .27(x+2)=42 | | 9a=9a | | 125+x+15=180 | | 3x+-2=4x+5 | | -42y=66 | | 42y=66 | | -8x-5y=-11 | | 81-x=27 | | 9a=a+60 | | 2b-b^2-15=0 | | 2(2x-8)-5=2(x-3)-1 | | 78507+11.25x=20885+23x | | 6N+6J=N | | 2a-11=3(a+1)+16a+5 | | 3x^2-13w-6w^2=0 | | v=2v-73 | | 7n+6=13+7n | | 16=-2(x+4) | | 5-13w-6w^2=0 | | 4u+18=2u+66 | | 0.20=ln(y) | | .25(x+4)=32 | | 9x^2-36=y | | 8u^2+1u-9=0 | | 28-8k=4(-1-k) | | 6x+-9=2x+7 | | 17x-7=13x+1 | | 6x+-9=2x+-7 | | 3.2=y+5.4 | | 9x-(6x+9)=7x-29 | | 5m-4=3(m+6) | | 4a-7=7(a+1)+14a+6 |